Students’ Ability in Reading Comprehension of Da’wah and Islamic Communication Department at STAIN Bengkalis - Mahsuri, Mahsuri (Kaisa: Jurnal Pendidikan dan Pembelajaran, 2021)
Reading as an important skill for students, especially in reading English texts that require more understanding than Indonesian texts. The function and importance of reading has changed both in society and in the world of education. This research was descriptive quantitative. The purpose of this research was to determine students’ ability in reading comprehension of the da'wah and Islamic communication department. The population in this research was all students who took study english text course in the second semester of the 2019/2020 school year with sample of 40 students. The data collection technique used reading comprehension test. The results of this research indicate that the students’ ability in reading comprehension in the da'wah and Islamic communication department is 48,875 which into avarage category. The difficult part of reading comprehension in this research was vocabulary. Students are expected to master and have a lot of vocabulary in English, it will be clearer in understanding the text in English. Not only vocabulary that must be mastered by students but there are several other factors that affect students' ability to understand reading.Membaca sebagai keterampilan penting bagi mahasiswa, terutama dalam membaca teks bahasa Inggris yang membutuhkan pemahaman lebih dari teks bahasa Indonesia. Fungsi dan pentingnya membaca telah berubah baik dalam masyarakat maupun dalam dunia pendidikan. Penelitian ini bersifat deskriptif kuantitatif. Tujuan penelitian ini adalah untuk mengetahui kemampuan pemahaman bacaan mahasiswa jurusan dakwah dan komunikasi Islam. Populasi dalam penelitian ini adalah seluruh mahasiswa yang mengambil mata kuliah Bahasa Inggris pada semester dua tahun ajaran 2019/2020 dengan sampel sebanyak 40 mahasiswa. Teknik pengumpulan data menggunakan tes pemahaman bacaan. Hasil penelitian ini menunjukkan bahwa kemampuan pemahaman bacaan mahasiswa jurusan dakwah dan komunikasi Islam adalah 48.875 yang berada pada kategori sedang. Bagian yang sulit dari pemahaman bacaan dalam penelitian ini adalah kosa kata. Jika siswa menguasai dan memiliki banyak kosakata dalam bahasa Inggris, maka akan lebih mudah untuk memahami teks dalam bahasa Inggris. Tidak hanya kosakata yang harus dikuasai siswa tetapi ada beberapa faktor lain yang mempengaruhi kemampuan siswa dalam memahami bacaan.